Prophylactic vs. Therapeutic Treatment With P2Et Polyphenol-Rich Extract Has Opposite Effects on Tumor Growth - Lasso, Paola; Gomez-Cadena, Alejandra; Urueña, Claudia; Donda, Alena; Martinez-Usatorre, Amaia; Barreto, Alfonso; Romero, Pedro; Fiorentino, Susana (Frontiers in Oncology, 2018)
Polyphenols have tumoricidal effects via anti-proliferative, anti-angiogenic and cytotoxic mechanisms and have recently been demonstrated to modulate the immune response through their anti- or pro- oxidant activity. Nevertheless, it remains controversial whether antioxidant-rich supplements have real beneficial effects on health, especially in complex diseases such as cancer. We previously identified a polyphenol-rich extract obtained from Caesalpinia spinosa (P2Et) with anti-tumor activity in both breast carcinoma and melanoma. The present work evaluated the ability of P2Et extract to modulate the immune system in either the steady state or following tumor challenge. We found that the prophylactic treatment of healthy mice increased the number of CD4+ and CD8+ activated T, NK, regulatory T, dendritic and myeloid-derived suppressor cells in lymphoid organs together with a significant increase in plasma IL-6. Interestingly, this pre-conditioning of the host immune system with P2Et did not involve a protective effect against the control of tumor growth and metastasis in transplantable models of melanoma (B16) and breast cancer (4T1), but in contrast, a detrimental effect was observed in both models. We further demonstrated that this effect was at least partly due to an increase in regulatory T cells, myeloid-derived suppressor cells, and proinflammatory cytokines, with a concomitant decrease in CD4+ and CD8+ T cells. Taken together, these results suggest that the anti-tumor and immunomodulation properties of the P2Et extract critically depend on the presence of the tumor and might be mediated by the complex interactions between the tumor cells and the other components of the tumor microenvironment.